2015
DOI: 10.1371/journal.pone.0128838
|View full text |Cite
|
Sign up to set email alerts
|

Aminobacter MSH1-Mineralisation of BAM in Sand-Filters Depends on Biological Diversity

Abstract: BAM (2,6-dichlorobenzamide) is a metabolite of the pesticide dichlobenil. Naturally occurring bacteria that can utilize BAM are rare. Often the compound cannot be degraded before it reaches the groundwater and therefore it poses a serious threat to drinking water supplies. The bacterial strain Aminobacter MSH1 is a BAM degrader and therefore a potential candidate to be amended to sand filters in waterworks to remediate BAM polluted drinking water. A common problem in bioremediation is that bacteria artificiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Therefore, future work should also aim to enhance the survival of exogenous organisms in augmented SSFs by either augmentation at successive stages of the SSF lifecycle (e.g., after biofilm maturation or SSF ripening) or through biostimulation of the estrogen-degrading bacteria which may allow for realistic scaling up to full-scale SSFs. Furthermore, building on the findings from Ekelund et al (2015) 55 who showed that the level of bacterial diversity in sand filters affected the degradation of BAM – a metabolite of the pesticide dichlobeni – future studies should explore the optimization of the bacterial diversity in augmented systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, future work should also aim to enhance the survival of exogenous organisms in augmented SSFs by either augmentation at successive stages of the SSF lifecycle (e.g., after biofilm maturation or SSF ripening) or through biostimulation of the estrogen-degrading bacteria which may allow for realistic scaling up to full-scale SSFs. Furthermore, building on the findings from Ekelund et al (2015) 55 who showed that the level of bacterial diversity in sand filters affected the degradation of BAM – a metabolite of the pesticide dichlobeni – future studies should explore the optimization of the bacterial diversity in augmented systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to “bottom-up” effects of bioaugmentative bacteria, such as in this SSF study, positive – and negative – “top-down” feedback mechanisms from a variety of meiofauna have been reported in the literature in the presence of xenobiotic chemicals. 53 , 55 , 60 …”
Section: Discussionmentioning
confidence: 99%
“…The most important ecological factor in bioaugmentation success has been postulated to be the invader’s ability to grow quickly and establish itself, reflected by the mineralization rate μ and the lag time λ, and not the total amount of accumulated mineralization A . Therefore, positive mineralization effects in pair-SFI co-cultures were defined as those increasing μ and decreasing λ, compared to the best-performing single-SFI co-culture, and vice versa for negative effects.…”
Section: Methodsmentioning
confidence: 99%
“…These two parameters have been highlighted as key to the success of bioaugmentation strategies and are more strongly linked with both positive and negative mineralization effects than the other mineralization parameters [25].…”
Section: Assessing Strain Interactionsmentioning
confidence: 99%
“…The latter option is justified by considering that the parameters represent different biological attributes and different underlying processes [25]. This is most noticeable in their opposing effects on mineralization performance in particular; an increased parameter λ is considered a negative effect while an increased parameter µ is considered a positive effect.…”
Section: Building the Competition Structuresmentioning
confidence: 99%